Investigation of combustion, performance and emission characters of compression ignition engine fuelled with diesel blends of linseed and cottonseed oil. (2017) - Kumar, C. Ramesh; Saravanan, S.; Gopal, P.
Environmental pollution and reducing fossil fuel reserves are the twin crisis that forces the automotive industry today to develop bio-based sustainable alternative fuel. This work aims to study the performance and emission characteristics of a direct injection diesel engine fuelled with blends of diesel, biodiesel blends derived from linseed oil and cottonseed oil as fuel. Four samples namely diesel, bio diesel blends of 5%, 10% and 15% which are referred as samples 1, 2, 3 and 4, respectively are used as fuel. Experimental study shows significant increase in smoke emission by around 24% and 47% with samples 3 and 4 when compared with sample 1. On average, reduction in unburned hydrocarbon emission by 52% and 37% was achieved with samples 2 and 3 when compared to sample 1. When compared to sample 1, NOx emission was observed to be reduced by 24% when the engine was operated with sample 4.